Fungus from a historical timber bridge in northern Sweden - Myronycheva, Olena; Björngrim, Niclas; Lin, Chia-Feng; Karlsson, Olov; Sandberg, Dick; Zalar, Polona; Gunde-Cimerman, Nina (Luleå tekniska universitet, Träteknik, 2023)
Funder: CT WOOD; ISBN for host publication: 978-961-6379-82-3